The Dwarfing Effects of Different Plant Growth Retardants on Magnolia wufengensis L.Y. Ma et L. R. Wang - Xiaodeng Shi (Forests, 2021)
: The effects of varieties, concentrations, and number of applications of plant growth retardants (PGRs) on the morphological, physiological, and endogenous hormones of Magnolia wufengensis L.Y. Ma et L. R. Wang were assessed to obtain the most suitable dwarfing protocol for M. wufengensis and to provide theoretical support and technical guidance for the cultivation and promotion of this species. One-year-old M. wufengensis ‘Jiaohong No. 2’ grafted seedlings served as the experimental materials. In the first part of the experiment, three PGRs (uniconazole, paclobutrazol, prohexadione calcium), three concentrations (500, 1000, 1500 ppm), and three applications (one, three, and five applications) were applied in dwarfing experiments to perform L9 (34) orthogonal tests. In the second part of the study, dwarfing experiments were supplemented with different high uniconazole concentrations (0, 1500, 2000, 2500 ppm). Spraying 1500 ppm uniconazole five times achieved the best M. wufengensis dwarfing effect, related indicators of M. wufengensis under this treatment were better than other treatment combinations. Here, M. wufengensis plant height, internode length, scion diameter, and node number were significantly reduced by 56.9%, 62.6%, 72.8%, and 74.4%, respectively, compared with the control group. This treatment increased superoxide dismutase (SOD) activity by 66.0%, peroxidase (POD) activity by 85.0%, soluble protein contents by 43.3%, and soluble sugar contents by 27.6%, and reduced malondialdehyde (MDA) contents by 32.1% in leaves of M. wufengensis compared with the control. The stress resistance of M. wufengensis was enhanced. The treatment also reduced gibberellin (GA3) levels by 73.0%, auxin (IAA) by 58.0%, and zeatin (ZT) by 70.6%, and increased (abscisic acid) ABA by 98.1% in the leaves of M. wufengensis. The uniconazole supplementation experiment also showed that 1500 ppm was the optimal uniconazole concentration. The leaves exhibited abnormalities such as crinkling or adhesion when 2000 or 2500 ppm was applied. Given the importance of morphological indicators and dwarfing for the ornamental value of M. wufengensis, the optimal dwarfing treatment for M. wufengensis was spraying 1500 ppm uniconazole five times.